Treatment of an Adult Skeletal Class III Patient with Surgically Assisted Rapid Palatal Expansion and Facemask - Hossein Behnia; Hossein Mohammad-Rahimi; Mohammad Behnaz (Case Reports in Dentistry)
This case report presents the treatment of a 21-year-old male patient with class III skeletal malocclusion, an open bite, and vertical growth pattern. He was managed with surgically assisted rapid palatal expansion (SARPE) along with an orthopedic facemask. The duration of treatment was 16 months. Significant improvement and favourable outcome were observed concerning both facial appearance and paraclinical parameters after completion of treatment.